Effectiveness of Kaffir lime (Citrus hystrix) and Citronelal (Cymbopogon nardus) Leaf Powder on Control of Rice Warehouse Pest (Corcyra cephalonica) - Nabila Seftia; Maria Heviyanti; Cut Mulyani (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2021)
The aim of the study was to determine the effectiveness of kaffir lime leaf powder (Citrus hystrix) and citronella (Cymbopogon nardus) against the control of rice warehouse pests Corcyra cephalonica. This research was conducted at the Basic Laboratory and Agrotechnology Laboratory of Samudra University from January to March 2021. This study used a Factorial Completely Randomized Design (CRD), which consisted of 2 factors: 1. Powder (S), S1 = Purut Jeruk Leaf Powder, S2=Serai Fragrant Powder, 2. Dosage of Kaffir lime leaf powder and fragrant lemongrass (D), D0 = Control, D1 = 15 grams, D2 = 20 grams, D3 = 25 grams, D4 = 30 grams, D5 = 35 grams. Based on the results of the study, it can be concluded that for controlling the rice warehouse pest C. cephalonica, it can be applied as a vegetable insecticide powder of kaffir lime leaves at a dose of 35 g.